Review of performance-based incentives in community-based family planning programmes. Issue 2 (18th July 2014) - Bellows, Nicole M; Askew, Ian; Bellows, Benjamin
Abstract : Background: One strategy for improving family planning (FP) uptake at the community level is the use of performance-based incentives (PBIs), which offer community distributors financial incentives to recruit more users of FP. This article examines the use of PBIs in community-based FP programmes via a literature search of the peer-reviewed and grey literature conducted in April 2013. Results: A total of 28 community-based FP programmes in 21 countries were identified as having used PBIs. The most common approach was a sales commission model where distributors received commission for FP products sold, while a referral payment model for long-term methods was also used extensively. Six evaluations were identified that specifically examined the impact of the PBI in community-based FP programmes. Overall, the results of the evaluations are mixed and more research is needed; however, the findings suggest that easy-to-understand PBIs can be successful in increasing the use of FP at the community level. Conclusion: For future use of PBIs in community-based FP programmes it is important to consider the ethics of incentivising FP and ensuring that PBIs are non-coercive and choice-enhancing.